Small hydropower plants as a threat to the endangered pearl mussel Margaritifera margaritifera - Sousa, Ronaldo (2020)
Freshwatermussels are undergoing rapid global declines due to habitat loss and fragmentation, among other factors, but little is known about the effects of small hydropower plants. Here we assessed the impact of small hydropower plants on the abundance and size structure of the imperilled pearl mussel Margaritifera margaritifera. For this, we sampled 66 sites in three Portuguese rivers (Mente, Rabaçal and Tuela) located upstreamand downstream of dams andwithin the reservoirs. Pearl musselswere significantly more abundant upstreamthan downstream of dams (97.4% more) or within reservoirs (98.5% more). In addition, juveniles were mostly found upstream of dams. The most significant environmental alterations that explained the observed patterns were related to changes in sediment characteristics (accumulation of fine sediments and organic matter in reservoirs) andwater chemistry, most notably suspended solids (highest values in reservoirs) and dissolved oxygen (lowest values in reservoirs). Overall, results show that small hydropower plants can deeply affect pearl mussel populations: specimens almost disappeared from the areas within the reservoirs and sites located downstream only retained adults without signs of recent recruitment. Future management measures devoted to the conservation of pearlmussels should take into account the results reported here to avoid the construction of newdamsin pearl mussel rivers; improve management of the river flow in downstream areas; and consider the decommissioning of dams in pearlmussel riverswith a particular attention devoted to the re-naturalization of river sections under the influence of the reservoir and downstream areas.